Evaluation of Paste and Dried Microalgae Biomass and Its Nutritional Value During Storage - Antara Nyoman Semadi; Gunam Ida Bagus Wayan; Suhendra Lutfi (BIO Web of Conferences, 2024)
Microalga has recently attracted considerable attention researchers and bio-industries for its potential nutrition properties as feed and food. Three kinds of microalgae namely Spirulina sp., Chaetoceros sp., and Chlorella sp., which have a potency to develop as a source of nutrition, were experimented to grow on the laboratory scale. Their biomass product was concentrated in the form of biomass paste and then dried in vacuum condition at 45°C. Biomass products were stored in paste and dry form for four weeks at 4°C. The result of the experiment showed that there were cells and nutritional changes during storage. After storage for 4 weeks, the viable cells on biomass paste detected were 60% and 46% for Chaetoceros sp. and Chlorella sp., respectively. Cell fragmentation of Spirulina sp. was occurred, on the other side, during storage. The protein content of biomass paste of microalgae and dried biomass as well were not significantly changed during storage, but the content of β-carotene and the antioxidant capacity of the biomass decreased during storage.